Characterization of the Solution Structure of Human Serum Albumin Loaded with a Metal Porphyrin and Fatty Acids - Junk, Matthias J.N. (The Biophysical Society, 2011)
The structure of human serum albumin loaded with a metal porphyrin and fatty acids in solution is characterized by orientation-selective double electron-electron resonance (DEER) spectroscopy. Human serum albumin, spin-labeled fatty acids, and Cu(II) protoporphyrin IX—a hemin analog—form a fully self-assembled system that allows obtaining distances and mutual orientations between the paramagnetic guest molecules. We report a simplified analysis for the orientation-selective DEER data which can be applied when the orientation selection of one spin in the spin pair dominates the orientation selection of the other spin. The dipolar spectra reveal a dominant distance of 3.85 nm and a dominant orientation of the spin-spin vectors between Cu(II) protoporphyrin IX and 16-doxyl stearic acid, the electron paramagnetic resonance reporter group of the latter being located near the entry points to the fatty acid binding sites. This observation is in contrast to crystallographic data that suggest an asymmetric distribution of the entry points in the protein and hence the occurrence of various distances. In conjunction with the findings of a recent DEER study, the obtained data are indicative of a symmetric distribution of the binding site entries on the protein's surface. The overall anisotropic shape of the protein is reflected by one spin-spin vector orientation dominating the DEER data.